Contingent factors that influence the use of management accounting practices in the portuguese textile and clothing sector - Leite, Akaísa (2018)
This scientific research aims to verify relationships in the use of management accounting practices and several contingent factors. Contingency theory was used in the analysis model. The study focused on 512 textile and clothing companies of the Associação Têxtil e Vestuário de Portugal (Portuguese Textile and Clothing Association). Data was collected in the middle of 2014 by means of a questionnaire. The results of the quantitative study showed that traditional management accounting practices are more commonly used than modern ones. In addition to the interdependence found between some of the variables in the analysis model, the results obtained by using the multiple linear regression model showed that advanced production technology influences, in a positive and direct way, the use of management accounting practices.